Women and Political Participation: Communal Elections in the Rif - Ammari, Abdelhak; Bouziane, Karima; Bouylmani, Ahmadou (International Journal of Language and Literary Studies, 2025)
Although Morocco has made great efforts to eradicate patriarchy, inequalities persist. Women in this country gained the right to vote in 1963, immediately after independence. From then on, different parts of Morocco have witnessed the pivotal role women have been playing in politics, actively calling for their rights and more reforms. Notwithstanding this, there are some parts of the country where women are reticent to talk and be involved in politics. Therefore, elections and campaigns are carried out somewhat without women and their voices, which are valuable solely when used by men to achieve their goals. In light of this, it is hypothesized that women who are living in Ait Hazem, a village belonging to the Rif region of Morocco, do not play an effective and pivotal role in politics. These women do not decide on whom to vote because their votes are only exploited by men close to them to attain their pragmatic goals. This emanates from the patriarchal nature of the community, women’s lack of education, the absence of women’s rights activists, and the deficiency of campaigns that sensitize women to the importance of elections.